PUTRI MURTI - Laksamana, Putu Diki; Bratanatya, I Bagus Wijna; Cempaka Dewi, Ni Luh Ayu (Pusat Penerbitan LP2MPP ISI Bali, 2025)
The story takes place in a realm called Uma Praksa, where a kingdom named Brahma Purana is ruled by Queen Ratu Putri. One night, during a royal meeting attended by Indurasmi, Ratu Putri recalls a tale told by the Brahmin Vishnu Yogi—that she can only be defeated by a powerful incantation known as Durga Murti Putri. The following night, Ratu Putri’s disciples, including Ni Sindur, gather at Setra Gandamayu for a ritual. After their meditation, Dewi Durga appears and grants them a divine blessing. They return to the palace, and later that night, Ratu Mohini, Raja Putra, Ni Condong, and Waraha Putra perform a sacred offering in Alas Putra, led by Ratu Mohini’s father, Sage Sri Nadaswara. During the ceremony, a thunderous roar surprises the assembly as Hayagriva, an avatar of Vishnu, descends. Meanwhile, Kala Boma summons Delem and Sangut to announce his plan to destroy Uma Praksa and its surroundings. That night, chaos unfolds as Kala Boma attacks the kingdom. Ratu Putri’s disciples and Raja Putra’s siblings, including Ratu Rupini and her allies, engage in fierce battle. Ratu Putri transforms into Rangda Putih, while Ratu Indurasmi becomes Rangda Bang or Durga Bang. The war rages for 108 days until Raja Putra, guided by Hayagriva, confronts and awakens his sister, Ratu Putri. Raja Putra then transforms into Banaspati (Barong). In their final transformation into Barong and Rangda, Raja Putra and Ratu Putri vanish, never returning to their human forms.